Sanitary sewage: Characterization, treatment and ecotoxicity - Lobo, Isadora Vitali; Américo-Pinheiro, Juliana Heloisa Pinê (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
The treatment and disposal of domestic sewage is one of Brazil's main challenges. Sewage composition varies with the habits of the population and the frequency with which new contaminants are released into the environment. This study is a bibliographical review of the main aspects related to the characterization and composition of sanitary sewage, types of sewage treatment systems and pertinent legislation; and toxicity of domestic effluents. The review was based on publications available on Science Direct, Google Scholar and Scielo, as well as on printed publications, relevant legislation, and normative instructions. The research period adopted for the selection of publications was from 2005 to 2021. We found out that, in addition to the levels of organic matter from domestic sewage, residues from products used in daily life, such as pharmaceuticals and cleaning products, can be found in effluents in concentrations harmful to the environment. Often, the types of treatment used in municipal sewage treatment plants do not efficiently remove these contaminants. Thus, even if sewage is treated to meet the limits required for the physical-chemical and biological parameters established by law, domestic effluent can present a high potential for toxicity to various aquatic species such as microcrustaceans, mollusks and fish. Thus, ecotoxicological analyses represent a remarkable mechanism for indicating the efficiency of removal of emerging contaminants present in treated sanitary effluent, in addition to indicating the deleterious effects caused by these residues to the environment and ecosystems associated with the receiving water body.